The influence of praying and singing before and after studying on the spirit of learning based on students' perceptions (case study at junior high school of Anugerah Abadi Pamulang, South Tangerang, Banten) - aspari aspari; Risa Prayudhi; Andriansah Andriansah (Sean Institute, 2024)
Praying and singing are activities commonly carried out by religious adherents in Indonesia. This habit can be carried into everyday life, including in learning and teaching activities in educational institutions. Singing is something that is commonplace nowadays. Even from childhood we have been accustomed to singing or at least listening to songs. If we look at our parents when their babies cry, quite a few of the mothers who are looking after their children sing, either just humming or even accompanied by music, with the aim of just making their babies calm down and stop crying. Meanwhile, prayer itself is a petition or request from a servant to God using the desired pronunciation and fulfilling the stipulated conditions. In this study, researchers raised the theme of praying and singing before and after studying and their influence on enthusiasm for learning based on students' perceptions. In conducting this research, researchers used questionnaire methods and literature study. Namely combining the results of the questionnaire with the opinions of experts.